Inconsistent staffing and its impact on service delivery in ASD early-intervention. (April 2017) - Sulek, Rhylee; Trembath, David; Paynter, Jessica; Keen, Deb; Simpson, Kate
Abstract: Background: Inconsistent staffing (high turnover, casual workforce) is problematic in organisations, with the potential to impact both staff and services provided. Research has primarily focused on the impacts of inconsistent staffing in child welfare and community services with little evidence surrounding their ability to impact the outcomes for children with Autism Spectrum Disorders attending early-intervention services. Aim: The aim of this study was to explore staff views regarding the impact of staff turnover on the delivery of group based early intervention for children with ASD. Methods and procedures: We conducted five focus groups involving 29 professional (e.g. teachers, behaviour therapists), para-professional (e.g. child care workers), and managerial staff to explore their views. Audio recordings were transcribed verbatim for use in thematic analysis. Outcomes and results: Two central themes, comprising five categories emerged to encompass participants' views. "Impacts on Staff" accounted for the challenges existing staff felt when working with new and untrained staff in the centre. Participants also expressed concerns for the "Impacts on Service Delivery" that resulted from dynamic staffing, affecting fidelity of interventions and the program itself. Conclusions and implications: The findings suggest that lacking a consistent staffing structure is problematic when attempting to provide high quality early intervention services to children with ASD and suggest that future research should investigate the extent of inconsistent staffing, impacts of inconsistent staffing on providing intervention, and develop a range of tools to help measure these effects.